UPAYA MENINGKATKAN KEMAMPUAN LITERASI DENGAN MENGGUNAKAN METODE PEMBELAJARAN POSTER COMMENT PADA MATA PELAJARAN IPS SISWA KELAS V (LIMA) SDN 10 CAKRANEGARA KOTA MATARAM TAHUN PELAJARAN 2022/2023 - Baiq Sarlita kartiani; M. Chairul Anam; Zulhadi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This classroom action research was conducted on the basis of several things that became the source, namely the low level of students' literacy skills, including the method used by the teacher which was still a conventional learning method, the lack of students' ability to obtain, process, and convey information in the learning process which led to the learning process becomes passive. Based on this background, it is to improve students' literacy skills that is the goal of conducting this classroom action research. To increase student literacy, the researcher applied the poster comment learning method to social studies for fifth grade students at SDN 10 Cakranegara, Mataram City. Then the data obtained is analyzed. This study consisted of two cycles, each cycle having 4 stages, namely the planning stage, the action stage, the observation stage and the reflection stage. The results of data analysis show that using the poster comment learning method can improve the literacy skills of fifth (five) grade students at SDN 10 Cakranegara for the 2022/2023 academic year. This is in accordance with student learning outcomes in cycle I obtained a percentage of 68% categorized as quite good while in cycle II there was an increase with a value of 95% categorized very well.